The resilience framework as a strategy to combat stress-related disorders. (November 2017) - Kalisch, Raffael; Baker, Dewleen; Basten, Ulrike; Boks, Marco; Bonanno, George; Brummelman, Eddie; Chmitorz, Andrea; Fernàndez, Guillén; Fiebach, Christian; Galatzer-Levy, Isaac; Geuze, Elbert; Groppa, Sergiu; et al.
Consistent failure over the past few decades to reduce the high prevalence of stress-related disorders has motivated a search for alternative research strategies. Resilience refers to the phenomenon of many people maintaining mental health despite exposure to psychological or physical adversity. Instead of aiming to understand the pathophysiology of stress-related disorders, resilience research focuses on protective mechanisms that shield people against the development of such disorders and tries to exploit its insights to improve treatment and, in particular, disease prevention. To fully harness the potential of resilience research, a critical appraisal of the current state of the art — in terms of basic concepts and key methods — is needed. We highlight challenges to resilience research and make concrete conceptual and methodological proposals to improve resilience research. Most importantly, we propose to focus research on the dynamic processes of successful adaptation to stressors in prospective longitudinal studies.